Father of the bride [videorecording (DVD)] - Lopez, Matt; Garcia, Andy; Estefan, Gloria; Arjona, Adria, 1992-; Merced, Isabela, 2001- (Warner Bros., 2022)
The story of a father coming to grips with his daughter's upcoming wedding through the prism of multiple relationships within a big, sprawling Cuban-American family.